Design and Study on 25 Gbit/s Optical Transmitter Module based on Silicon Optical Scheme - Xuan-xuan CHENG; Jian-yi ZHAO; Xi XIAO; Miao-feng LI; Lei WANG; Bo ZHANG; Chuan SHI; Lei-lei HU; Jing CAI (Guangtongxin yanjiu, 2021)
With the rapid development of optical communication technology, the capacity of optical transmission increases dramatically. The flexible requirements for the management and scheduling of Dense Wavelength Division Multiplexing (DWDM) network systems also become higher. The wavelength adjustable module can meet the requirements of flexible network management, which will be widely used in Wavelength Division Multiplexing (WDM) system and 5G network. As the core component in the module, the research of tunable laser is particularly important. This paper introduces the hybrid integrated package technology of tunable laser and silicon modulator chip, which uses the design of an etalon a gluing standard to control the wavelength, saving the design of semiconductor refrigerator and the package size. The tunable laser produced meets the wavelength output requirements of ITU-96 channel, and the eye map meets the working eye map of 100 G Base-LR4 international standard.